COVID-19 CONSPIRACISM IN THE AGE OF POST-TRUTH - Ömer Ersin Kahraman (Felsefe Dünyası)
The Covid-19 pandemic has triggered one of the most important structural crises of the world as the pandemic has not just had a great impact on the healthcare systems, but it has overwhelmed the world economically, politically and socially due to the extreme measures applied to mitigate the propagation of the virus. This situation has led to numerous debates around the effects of the pandemic and the methods that states applied to deal with it, not only in academic circles but in all levels of society merely throughout social media discussions to which participation does not require any educational or professional background. Consequently, this period has also witnessed the diffusion of conspiracy theories varying from accusations which consider the rapid propagation of the virus as a plot of states and big pharmaceutical companies to allegations which presume the pandemic as a hoax to implement new communication technologies like 5G. It is obvious that this situation misleads people and endangers the struggle against the propagation of the virus. At first glance, it can be thought that the use of new communication technologies is to blame for the diffusion of false news, and a solution can be found in developing new tools to detect hoaxes beforehand. However, although social media facilitates the diffusion of conspiracism, it cannot be taken as the major reason seeing the fact that people have chosen to use social media platforms as their information sources because of their distrust against the mainstream media insomuch as information itself has been commodified in the age of information. Thus, this article aims to investigate within a philosophical perspective the sociopsychological mechanisms of the propensity towards conspiracy theories in the post-truth era in relation with the lost faith in the Enlightenment project’s quest for universal truths due to the commodification and exploitation of information.